PENGARUH UKURAN PERUSAHAAN, LABA RUGI, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG (Studi Kasus pada Perusahaan Manufaktur di sektor Food and Beverages yang Terdaftar di BEI Tahun 2015-2018) - Yulian, Tri Nur Indahyanti; Sutarti; Pramesta, Sindi Indah (JURNAL EKONOMI, 2020)
This study aims to determine the effect of Company Size, Profit and Loss, and Audit Opinion on Audit Report Lag. The population in this study are manufacturing companies in the food and beverages sector which were listed on the Indonesia Stock Exchange in 2015-2018. The period used in this study was 4 years, starting in 2015-2018 in manufacturing companies in the food and beverages sector on the Indonesia Stock Exchange. The sample selection technique uses a purposive sampling method. The type of data used is secondary data and the total sample used in this study is 40 samples that have been selected based on predetermined criteria. The data analysis method used is multiple linear regression analysis. The results of this study indicate that: 1. Company size has no effect on Audit Report Lag 2. Profit and Loss has no effect on Audit Report Lag 3. Audit Opinion influences Audit Report Lag 4. Firm Size, Profit and Loss Opinion and Audit Opinion simultaneously influence Audit Report Lag. Future studies are suggested to be able to expand the research sample, add variables and extend the study period. Keywords: Company Size, Profit and Loss, Audit Opinion, Audit Report Lag